Types E and C of pigmentary demarcation lines in two Chinese sisters. - Xu, C.; Zhang, R.; Zhu, V. (European Journal of Pediatric Dermatology, 2014)
Pigmentary demarcation lines (PDLs), also known as Futcher or Voigt lines, present as an abrupt transition between areas of light and dark pigmentation. They consist of eight specific patterns, labeled A through H, among which types C and E are hypopigmented markings. In this paper, we described two girls with some bizarre hypopigmentation on their chest. Based on the clinical features, these lesions were diagnosed as types E and C of PDLs. No similar lesions were observed in their parents and younger brother. To our knowledge, types E and C of PDLs occurring in Chinese siblings have not previously been reported. We hope that the observation would help to understand the pathogenesis of PDLs.